Developing dimensions for a multicomponent multidisciplinary approach to obesity management: a qualitative study - Anita J. Cochrane; Bob Dick; Neil A. King; Andrew P. Hills; David J. Kavanagh (BMC, 2017)
Abstract Background There have been consistent recommendations for multicomponent and multidisciplinary approaches for obesity management. However, there is no clear agreement on the components, disciplines or processes to be considered within such an approach. In this study, we explored multicomponent and multidisciplinary approaches through an examination of knowledge, skills, beliefs, and recommendations of stakeholders involved in obesity management. These stakeholders included researchers, practitioners, educators, and patients. Methods We used qualitative action research methods, including convergent interviewing and observation, to assist the process of inquiry. Results The consensus was that a multicomponent and multidisciplinary approach should be based on four central meta-components (patient, practitioner, process, and environmental factors), and specific components of these factors were identified. Psychologists, dieticians, exercise physiologists and general practitioners were nominated as key practitioners to be included. Conclusions A complex condition like obesity requires that multiple components be addressed, and that both patients and multiple disciplines are involved in developing solutions. Implementing cycles of continuous improvement to deal with complexity, instead of trying to control for it, offers an effective way to deal with complex, changing multisystem problems like obesity.